ANTI-FATIGUE EFFICACY OF CROCIN IN MICE VIA REGULATION OF NRF-2/HO-1 PATHWAY-MEDIATED OXIDATIVE STRESS - Ming,Liu (2022)
ABSTRACT Introduction: Fatigue is a manifestation of sub-health status, which causes serious negative effects in daily life. The antioxidant properties of crocin have been widely investigated in many diseases. However, no correlation between crocin and fatigue was reported. Objective: To verify the anti-fatigue efficacy of crocin in swimming-induced exhaustive time. Materials and Methods: In this study, mice were treated with crocin for 28 days to assess its anti-fatigue efficacy. Exhaustive time, fatigue-relevant biochemical indices, inflammatory cytokines, energy metabolism indicators, oxidation parameters, and the NRF-2/HO-1 pathway were analyzed to explore evidence of crocin in high-intensity exercise. Results: Our research indicated that crocin dramatically extended swimming-induced exhaustive time. In strenuous swimming, crocin clearly eliminated BLA and SUN to maintain internal environment homeostasis, while it markedly improved glycogen concentrations in the muscles and liver to promote energy reserves. Moreover, crocin visibly improved the inflammatory reaction, as represented by reductions in TNF-a and IL-6, promoting endurance capacity. In the muscles, crocin noticeably enhanced SDH and Na+K+-ATP activities to improve energy metabolism in strenuous swimming. Lastly, crocin markedly improved SOD and CAT activities via the NRF-2/HO-1 pathway to defend against oxidative stress-induced fatigue. Conclusions: Crocin provides oxidation resistance and can be developed into anti-fatigue nutriments. Evidence level II; Comparative prospective study.